Pengaruh Komitmen Organisasi, Kepuasan Kerja Dan Budaya Organisasi Terhadap Organizational Citizenship Behaviour (OCB) Pada Karyawan Perusahaan Perum Bulog Padang - Rio Andhika Putra; Robby Dharma (Journal Of Science Education And Management Business, 2022)
The purpose of this study was to analyze the effect of organizational commitment, job satisfaction and organizational culture on the Organizational Citizenship Behavior (OCB) of employees of Perum Bulog Padang. The design of this research is in accordance with the research objectives and the problems being researched and formulated, the research that the author makes using quantitative methods. With a significant level of 0.001 less than 0.05, then H0 is rejected and Ha is accepted. That there is a positive and insignificant effect between Organizational Commitment to Organizational Citizenship Behavior (OCB) of Perum Bulog Padang. With a significant level greater than alpha (0.882 > 0.05). That there is a positive and significant influence between Job Satisfaction on Organizational Citizenship Behavior (OCB) of Perum Bulog Padang. With a significantly smaller level of alpha (0.000 < 0.05). That there is a positive and insignificant influence between Organizational Culture on Organizational Citizenship Behavior (OCB) of Perum Bulog Padang. With a significantly less than alpha level (0.068 > 0.05). Simultaneous Testing (F-Test) can be done by comparing the value of Fcount with Ftable because the value of Fcount is greater than the value of Ftable (12.335 > 2.92). The F value is 2,045 with a significant level of 0.000 less than 5%. Then Ho is rejected and Ha is accepted, which means this is done jointly between Organizational Commitment (X1), Job Satisfaction (X2), Organizational Culture (X3) and Organizational Citizenship Behavior (OCB) (Y).